2019
DOI: 10.1002/wdev.359
|View full text |Cite
|
Sign up to set email alerts
|

The significance of sponges for comparative studies of developmental evolution

Abstract: Sponges, ctenophores, placozoans, and cnidarians have key evolutionary significance in that they bracket the time interval during which organized animal tissues were first assembled, fundamental cell types originated (e.g., neurons and myocytes), and developmental patterning mechanisms evolved. Sponges in particular have often been viewed as living surrogates for early animal ancestors, largely due to similarities between their feeding cells (choanocytes) with choanoflagellates, the unicellular/colony‐forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 150 publications
1
8
0
Order By: Relevance
“…Together with observations that endopinacoderm-lined water canals can remodel in response to water flow dynamics (49,50), these data support a model in which MRTF-mediated environmental feedback mechanisms drive the development of the endopinacoderm. We speculate that this could be the rule rather than the exception in sponges, and it is conceptually plausible that this reflects the ancestral condition.…”
Section: The Origin and Ancestry Of Myocytessupporting
confidence: 66%
See 1 more Smart Citation
“…Together with observations that endopinacoderm-lined water canals can remodel in response to water flow dynamics (49,50), these data support a model in which MRTF-mediated environmental feedback mechanisms drive the development of the endopinacoderm. We speculate that this could be the rule rather than the exception in sponges, and it is conceptually plausible that this reflects the ancestral condition.…”
Section: The Origin and Ancestry Of Myocytessupporting
confidence: 66%
“…Finally, the role of MRTF in endopinacoderm differentiation helps to explain the plasticity and regenerative capacity of sponge tissues. Evidently without the need for the intrinsic positional cues characteristic of embryogenesis, sponges can develop normally from archeocyte-enriched aggregates and from gemmules, and adult tissues can remodel in response to flow dynamics 43,44 , 45,46 . In vertebrates, MRTF is an actin-regulated force-sensor involved in muscle plasticity and regeneration 21,47,48 , and our data indicate that similar mechanisms are operating in E. muelleri.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike hypothesized homologies between ciliates and animals, the inferred homology of the collar complex in animals and choanoflagellates survived molecular and biochemical analyses, which confirmed that the collar is composed of homologous cytoskeletal filaments in both choanoflagellates, sponges, and other animals (reviewed in (Brunet and King 2017;Leadbeater 2015)). The hypothesis of the homology of the collar complex -proposed on morphological grounds in the 19 th century -thus appears to have been predictive (Colgren and Nichols 2020) and is now accepted by most authors (but see (Mah, Christensen-Dalsgaard, and Leys 2014;Sogabe et al 2019) for exceptions and (Brunet and King 2017; Colgren and Nichols 2020; Myers 2019) for responses).…”
Section: Th Century: the Collared Flagellate/choanoblastaea Modelmentioning
confidence: 99%
“…Though the soma-germline distinction is blurry in some eusocial lineages (e.g. in the ant taxa of Harpegnathus and Ooceraea where workers retain some reproductive potential) the same can be said of many multicellular organisms (plants, worms, sponges) [19][20][21] .…”
Section: Colony Organization = Social Anatomy + Social Physiologymentioning
confidence: 99%